STUDI POTENSI PENYISIHAN NITROGEN PADA EFLUEN IPAL DOMESTIK DENGAN PENGGUNAAN CONSTRUCTED WETLAND (Studi Kasus : IPAL Bojongsoang, Bandung) - Yandes Panelin (Journal of Environmental Engineering and Waste Management, 2017)
The purpose of this research was measuring the treatment efficiency, determining the optimum operating conditions, determining the criteria for water reuse. This research is conducted in the laboratory using a constructed wetland with type of plant is Typha latifolia. Variations are made in this study are detention time (1day, 3days and 5 days) and type of reactors (constructed wetland & aerated constructed weland). Each reactor is given wastewater feed derived from effluent of WWTP Bojongsoang. The research was a sequenced of previuos reserach ( Panelin 2016). Parameters examined in this study are COD, NTK, Nitrate, Nitrite, Ammonium, pH, and temperature. Measurement of COD, pH, and temperature are conducted every day, while  NTK NTK, Nitrate, Nitrite,and Ammonium are done after the reactor reaching steady state conditions. Based on the measurements, the best pollutant elimination occurs on detention time of 5 days. The Nitrite pollutant removal efficiency is 96.7%. Ammonium pollutant removal efficiency is 89.1%. NTK pollutant removal efficiency is 86.2% . Constructed wetland reactor with additional aeration can remove nitrogen parameters better than the reactor without additional aeration.